An Initial Report on Operability and Safety of A Domestic Automated Peritoneal Dialysis Machine in Thailand - Traitanon, Opas; Boongerd, Thanarak; Dumnin, Songphon; Buekban, Chatchai; Pongthornseri, Ronachai; Sampnyuth, Supat; Thanawattano, Chusak; Surangsrirat, Decho (Asian Medical Journal and Alternative Medicine, 2021)
Background: Thailand had implemented the peritoneal dialysis first (PD first) policy which allowed access to peritoneal dialysis as a first-line treatment for end-stage renal disease (ESRD). However, all the patients under this policy are allowed to use only the self-operated Continuous Ambulatory Peritoneal Dialysis (CAPD) but not the Automated Peritoneal Dialysis (APD). While APD has a lot of advantages over CAPD, its cost is more than double in Thailand. Under these circumstances, it is crucial to produce APD equipment with a trade-off between good performance and affordable price. Methods: This study is a pilot cross-sectional study to evaluate the operability and safety of the domestically developed APD machine. Three stable ESRD patients already treated with APD machines were recruited for the 7-day trial. Results: There is a slight decrease in the dwell time due to the longer operational time of the developed machine; 11.26 ± 2.29%. Increases in serum creatinine and blood urea nitrogen were observed; 3.01 ± 1.83% and 22.92 ± 4.48%, respectively. No major adverse events were reported. Conclusion: The developed machine used only gravity for the exchange, the dwell time was decreased as expected, resulting in a lower exchange of the waste products from the blood to the peritoneal cavity. Even though the results show a slightly lower treatment performance, no clinical significance during short-term follow-up was observed. To obtain similar performance for the domestically developed APD machine, total treatment time could be increased to maintain comparable dwell time overnight.